Fracture morphology and toughening mechanism of Al2O3/ZrO2 eutectic ceramic prepared by the combustion synthesis under ultra-high temperature. (June 2019) - Zheng, Yongting; Yu, Wanjun; Yu, Yongdong; Su, Xiaoyue; Yang, Pan
Abstract: Al2 O3 /ZrO2 (ZrO2 :47.37 mol%) eutectic ceramic with fine and uniform microstructure was fabricated by combustion synthesis under ultra-high temperature. The fracture toughness and Vickers Hardness reached 10.6 ± 0.49 MPa·m 1/2 and 17.8 ± 0.61 GPa, respectively. The fracture morphology and toughening mechanism are investigated. When cracks meet rod-like ZrO2, the expansion path would deflect along the interface with a slip for a certain distance, while part of the rod-like ZrO2 will be pulled out. The effect of rod-like ZrO2 toughening, residual compressive stress toughening and t-ZrO2 phase transformation toughening is discussed. The toughening mechanism of rod-like ZrO2 includes crack deflection and fiber pull-out. The relevant calculated results show that the pull-out of rod-like ZrO2 makes the largest contribution to toughness, while the residual stress toughening makes the smallest contribution. For t-m transformation toughening, the size of transformation is estimated by XRD method. The calculated value of fracture toughness is 10.25 MPa·m 1/2 . Compared with the measured value of toughness, there is an error of 0.35 MPa·m 1/2 . Highlights: The Al2 O3 /ZrO2 eutectic ceramic with fine microstructure was prepared via ultra-high temperature combustion synthesis. Based on the investigation of the fracture morphologies, there toughening mechanisms were detailed discussion. A theoretical model was established to estimate the value of each toughing mechanism.